Antimicrobial Biphasic Polymer Coatings Enabled by Fast Diffusion of Active Compounds - Gross, Adam F (Langmuir : the ACS journal of surfaces and colloids, 2024)
The recent COVID-19 pandemic and the prospect of future global pandemics highlight the long-standing need to passively eliminate viruses and bacteria on surfaces. Conventional antimicrobial surfaces and coatings are typically constrained by a trade-off between antimicrobial efficacy and physical durability. A biphasic polyurethane coating has been developed that breaks this trade-off by incorporating a durability-imparting polycarbonate (PC) discrete phase with a continuous poly(ethylene glycol) (PEG) transport phase that absorbs, stores, and releases antimicrobial active compounds for extended microbial inactivation. The biphasic polymer was shown to absorb carboxylic acid and quaternary ammonium antimicrobial active compounds, maintained their levels after five years of simulated cleaning, and inactivated up to 99.99% of Human Coronavirus 229E and Influenza A H1N1. Furthermore, the levels of antimicrobial active compounds on the biphasic coating could be augmented by cleaning the substrate with a disinfectant. The practicality of biphasic coatings for automotive and commercial aerospace environments was demonstrated by showing control of hardness and stain resistance through biphasic composition, showing environmental durability through heat, humidity, and light exposure, and passing flammability protocols